Impact of the reemergence of North Pacific subtropical mode water on the multi-year modulation of marine heatwaves in the North Pacific Ocean during winter and early spring - Yong-Jin Tak; Hajoon Song; Yang-Ki Cho (Environmental Research Letters, 2021)
Marine heatwaves (MHWs), which are characterized by extremely warm water, can harm the marine ecosystem and fishing industry; improving the prediction of such events could reduce their harmful impact. In this study, we examined MHWs occurring in the North Pacific in winter/early spring, and their relationship with North Pacific subtropical mode water (STMW), based on the data analysis and numerical experiments. The time-lagged correlation between the cumulative intensity of MHWs and volume of STMW in March of each year suggests that STMW can modulate MHWs for up to three years after its formation. A patch of statistically significant negative correlation initially appeared in the formation region of the STMW but was found to the east of it near the Transition Zone Chlorophyll Front (TZCF) after one year. This patch stagnated near this remote site in the second winter and early spring. Passive tracer experiments using a numerical model indicate that the STMW, formed near the Kuroshio Extension in March, moves to the east underneath the mixed layer and is entrained to the surface in the following winter while altering the properties of STMW. The STMW reemerges in the second winter, after stagnating under the mixed layer near the TZCF. This suggests that the reemergence of STMW can suppress MHWs in the North Pacific during winter and early spring by reducing the sea surface temperature; if the volume of STMW is anomalously low, there is a greater likelihood of the occurrence of MHWs near the TZCF in the following two winters and early springs. Our results indicate that understanding STMW formation is crucial for predicting MHWs in the North Pacific Ocean during winter and early spring.